Segmental ureterectomy for high-risk ureteral carcinoma: a preliminary report - Wei Wei; Junfeng Liu; Lingdian Wang; Xiaoyu Duan; Degang Ding (BMC Urology, 2023)
Abstract Background EAU guidelines strongly recommend kidney sparing surgery (KSS) as the primary treatment option for the low-risk UTUC patients. While there are few reports involving the KSS treated for the high-risk counterparts, especially the ureteral resection. Objective To evaluate the effectiveness and safety of the segmental ureterectomy (SU) for the patients with high-risk ureteral carcinoma. Materials and methods We included 20 patients from May 2017 to December 2021 who underwent segmental ureterectomy (SU) in Henan Provincial People’s Hospital. The overall survival (OS) and progression free survival (PFS) were evaluated. Besides, the ECOG scores and postoperative complications were also included. Results As of December 2022, the mean OS was 62.1months (95%CI:55.6-68.6months) and the mean PFS was 45.0months (95%CI:35.9-54.1months). The median OS and median PFS were not reached. The 3-year OS rate was 70% and the 3-year PFS rate was 50%. The percentage of Clavien I and II complications was 15%. Conclusion For the selected patients with high-risk ureteral carcinoma, the efficacy and safety of segmental ureterectomy were satisfactory. But we still need to conduct prospective or randomized study to validate the value of SU in patients with high-risk ureteral carcinoma.